Penerapan Hukuman Mati terhadap Narapidana Lanjut Usia Ditinjau dari Hak Asasi Manusia - Romadhon Dwi Saputra, Fitrian; Subroto, Mitro (CV RIFAINSTITUT, 2021)
Law as a tool to change society or social engineering. Indonesia as a State of Law with Positive Law, namely the Criminal Code still imposes criminal sanctions in the form of the death penalty. In essence, the death penalty is a punishment by eliminating the life of the convict. However, the application of the death penalty creates a causa celebre (trigger) for the re-emergence of polemics against the pros and cons of the death penalty decision. This is especially true for elderly prisoners. Because there are provisions regulated in Law No. 13 of 1998 concerning Elderly Welfare which discusses the rights of elderly convicts. Then from the perspective of human rights, the death penalty is not inconsistent with national or international legal instruments, such as the 1945 Constitution, Law No. 39/1999 on Human Rights, the 1948 Universal Declaration on Human Rights, and the International Covenant on Civil Rights. and Political Rights 1966. The method used in this paper is normative juridical and analytical descriptive.